PENERAPAN MANAJEMEN TEKNIK INFORMASI PENDIDIKAN ISLAM DALAM PROSES PEMBELAJARAN DI SMK HARAPAN 1 RANCAEKEK BANDUNG - Uwoh Saepuloh (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2020)
The purpose of this study was to determine the application of management of Islamic education information techniques in the learning process at SMK Harapan 1 Rancaekek Bandung. This study uses a qualitative approach with descriptive methods. The results of the research show that: 1) The application of management information systems is very important in educational institutions, especially at SMK Harapan 1 Rancaekek Bandung using data processing applications, namely dapodic and information techniques in supporting the learning process to provide educational services by facilitating practice learning using technology infrastructure, such as learning facilities by integrating computers 2) The learning process in this school, namely, before implementing the learning process must go through three stages, namely, first, the planning stage. In this stage, make an effective day analysis and analysis of learning programs, make an annual program, compile a syllabus, prepare lesson plans, and make learning assessments. Second, the implementation stage. In this stage what needs to be done, namely, aspects of the approach in learning, aspects of strategy and tactics in learning, aspects of methods and techniques in learning. The learning media used in the learning process are printed media (books), pictures, LCD and computers. Third, the evaluation stage. In this stage, what is evaluated is learning knowledge that is tested by writing, orally, and a list of exam questions. Evaluation of learning skills that are evaluated by practical exams, and analysis of assignments that are self-evaluated by the educator. And the form of tests given to students must still be with standard requirements.